Tradisi Pembacaan Ayatul Hirzi: Studi Living Qur’an Di Pondok Pesantren Putri Ustman Bin Affan Laud Dendang - Siti Ramah; Abu Sahrin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This article aims to discuss the living Qur'an in the form of the practice of Ayatul Hirzi at the Putri Ustman bin Affan Islamic Boarding School as a mandatory program for female students and explain the impact of dzahir and inner thoughts felt by female students. This research uses a qualitative method with a descriptive approach. This study combines a literature study which is Ayatul Hirzi's reference source and a field study which uses the Ustman bin Affan Putri Islamic Boarding School as the object of study. Research informants ustad/dzah, caregivers and students. Data collection techniques using interviews, documentation and observation. The research results show that the practice of reading Ayatul Hirzi has become a mandatory tradition as an effort to protect oneself. The practice of reading Ayatul Hirzi has produced a positive impact mentally and spiritually in the form of a feeling of security and protection from bad influences that might befall.